Assessment of Protection Issues in Active Distribution Networks With Cyber Attack-Induced OLTC Operations - Prasad U.; Mohanty S.R.; Singh S.; Singh S.P. (My University, 2025)
The primary objective of this study is to analyze the intricate interplay among on-load tap changer (OLTC) transformers, photovoltaic (PV) systems, protection infrastructure, and cybersecurity in modern active distribution network (ADN). OLTC is a pivotal component in power systems, contributing significantly to various aspects such as voltage regulation, grid stability, line loss reduction, integration of renewable energy sources and so forth. Smart grid strategies, including volt/VAR optimization (VVO) and conservation voltage reduction (CVR), are predominantly implemented through tap position adjustments to achieve energy conservation and alleviate peak load demands. While extensive research has focused on optimizing the deployment of these techniques using OLTC transformers in ADN, limited attention has been given to their impact on protective infrastructure functionality. Additionally, centralized control schemes, reliant on dedicated communication infrastructure and contemporary protocols, raise concerns regarding vulnerability to cyber-attacks targeting tap control signals. This research addresses these gaps by employing a real-time simulation platform and commercial equipment to conduct a comprehensive impact analysis of attack-induced OLTC operation on an overcurrent protection scheme within a modified IEEE 34-node test feeder incorporating PV. Subsequently, it validates the proposed interior point method-based robust overcurrent protection approach. © 1972-2012 IEEE.